1974
DOI: 10.1071/ar9740219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed inoculation with Bacillus subtilis and Streptomyces griseus on the growth of cereals and carrots

Abstract: The effect of Bacillus subtilis A13 and Streptomyces griseus 2-A24 on the yield of cereals and carrots was studied. The organisms, both antagonistic to Rhizoctonia solani, were applied individually to barley, oats and wheat for sowing at three sites with a known incidence of R. solani. Root disease was not effectively controlled, yet the seed treatments increased grain yield and dry matter production at one site, advanced time of heading at another site and increased tiller number at two sites. Evidence was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(45 citation statements)
references
References 3 publications
2
40
0
3
Order By: Relevance
“…Marketable yields were increased over controls by 17% and 15% in two separate field trials. Specifically, both trials also indicated an increased yield of large and very large grade carrots over controls (Merriman et al 1974). Nearly 20 yr later, El-Abyad et al (1993) described the use of three Streptomyces spp.…”
Section: Actinomycetes As Pgprmentioning
confidence: 99%
See 3 more Smart Citations
“…Marketable yields were increased over controls by 17% and 15% in two separate field trials. Specifically, both trials also indicated an increased yield of large and very large grade carrots over controls (Merriman et al 1974). Nearly 20 yr later, El-Abyad et al (1993) described the use of three Streptomyces spp.…”
Section: Actinomycetes As Pgprmentioning
confidence: 99%
“…for the improvement in tomato growth, although this was not formally tested (El-Abyad et ai 1993). While thèse studies by El-Abyad et al (1993) and Merriman et al (1974) reported plant growth enhancement as a function of inoculation with Streptomyces, neither they investigated the inoculum under gnotobiotic conditions, nor the possible mechanisms of streptomycete-mediated growth promotion.…”
Section: Actinomycetes As Pgprmentioning
confidence: 99%
See 2 more Smart Citations
“…For eg. as early as 1974, Merriman et al reported the use of a strain of Streptomyces griseus, which was originally selected for the biological control of Rhizoctonia solani, as a seed treatment for barley, oat, wheat and carrot, in order to increase their growth (Merriman et al, 1974). Similarly El-Abyad et al, (1993) described the use of three Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%